DETERMINATION OF PERCEIVED STRESS LEVELS AND COPING WITH HUMOR IN CANCER PATIENTS RECEIVING CHEMOTHERAPY - Ersoy, Mustafa; Kirca, Kami̇le; Kaş, Canan; Sözeri̇ Öztürk, Eli̇f (Iktisadi Kalkinma ve Sosyal Arastirmalar Dernegi, 2023)
This study aims to determine perceived stress levels and coping with humor in cancer patients receiving chemotherapy. This descriptive study was conducted in a single center in Turkey and involved a total of 135 patients who had been diagnosed with cancer. The patients receiving chemotherapy had high levels of perceived stress and their use of humor as a coping strategy in stressful situations was below average. The perceived stress scale score was statistically significantly associated with age, employment status, presence of chronic disease, frequency of chemotherapy sessions and receipt of radiotherapy (p <0.05). The coping humor scale score was statistically significantly associated with age, education, economic status, previous hospitalization and time since diagnosis (p <0.05). Increasing the awareness of patients about humor and the use of humor starting from the time of cancer diagnosis can positively affect treatment and follow-up.
Keywords: 3. Good health